Respostas
respondido por:
1
d = raiz de [(x2 - x1)^2 + (y2 - y1)^2]
d = raiz de [(- 6 - 6)^2 + (1 - 6)^2]
d = raiz de [( - 12)^2 + (- 5)^2]
d = raiz de [144 + 25]
d = raiz de [169]
d = 13
Espero ter ajudado, bons estudos!
d = raiz de [(- 6 - 6)^2 + (1 - 6)^2]
d = raiz de [( - 12)^2 + (- 5)^2]
d = raiz de [144 + 25]
d = raiz de [169]
d = 13
Espero ter ajudado, bons estudos!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás